Interviewing a Person with Bipolar Disorder Under Involuntary Commitment: A Case Report. (December 2019) - Gather, Jakov; Kalagi, Janice; Otte, Ina; Juckel, Georg
In this case report, we report an ethical problem that we faced in the course of an interview study on open-door policies in psychiatry with persons under involuntary commitment. One of the interviewees was a young woman with bipolar disorder who was under involuntary commitment at the time of the interview. While the woman had been assessed as competent and gave informed consent to research participation, her manic symptoms increased when the interview became increasingly distressing for her. Because of this, we decided to break off the interview and resume it at a later point of time. Within the research team, we raised the following ethical questions: (1) Was the participant, contrary to the initial assessment, unable to give consent for the study? (2) Was the voluntariness of her research participation compromised by her manic symptoms and involuntary commitment? (3) Should the participant have been excluded from the study against her expressed wish? (4) Should we have refrained from interviewing persons who were still under involuntary commitment?